2009
DOI: 10.1111/j.1478-3231.2008.01794.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between combinations of glutathione‐S‐transferase M1, T1 and P1 genotypes and non‐alcoholic fatty liver disease

Abstract: This is the first report to show the impact of the GSTs genotypes on the development of NAFLD. This finding, which should be confirmed in further studies in larger populations, may help to develop a more targeted prevention programme at an early stage for subjects with an increased risk for NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 29 publications
1
14
1
Order By: Relevance
“…Also, the combined effect of the GSTP1 and GSTM1 variant genotypes on the risk of AD tended to be higher than the effect of GSTP1 or GSTM1 variants alone. Similar to our findings, several studies have indicated that the influences of GST genotypes on disease risk become more significant with an increase in the number of GST variant alleles (29)(30)(31). This is likely due to GST enzymes having similar substrate specificities.…”
Section: Discussionsupporting
confidence: 79%
“…Also, the combined effect of the GSTP1 and GSTM1 variant genotypes on the risk of AD tended to be higher than the effect of GSTP1 or GSTM1 variants alone. Similar to our findings, several studies have indicated that the influences of GST genotypes on disease risk become more significant with an increase in the number of GST variant alleles (29)(30)(31). This is likely due to GST enzymes having similar substrate specificities.…”
Section: Discussionsupporting
confidence: 79%
“…Any disharmony in the pathways involved in triacylglycerol release, synthesis or oxidation could contribute to its accumulation in the liver (46). NAFLD is the most common reason for abnormal liver function, and may occur in 10-30% of the population (47). Amassment of triglycerides inside hepatocytes, chronic oxidative stress levels, insulin resistance, inflammation and fibrosis in combination make NAFLD a complicated disease (48).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, GSTs have a lower expression in Caucasians compared to African–Americans, who have a lower prevalence of NAFLD (Stepanova et al, 2010). The GSTM1 -null genotype, shown to confer a higher risk of T2D, is also present at a higher frequency in NAFLD subjects compared to control (Hori et al, 2007, 2009). Thus, decreased activity of GSTs play a plausible role in NAFLD progression as a result of increased damage by oxidative stress (Table 3).…”
Section: Nafld and Drug Dispositionmentioning
confidence: 99%